Theoretical Review of the Impact of Fiscal Deficits on Economic Growth in Nigeria - Musa, Bushi Kasimu (European Scientific Journal, ESJ, 2021)
The growth and persistence of fiscal deficits in both the industrialized and developing countries has brought the issue of fiscal deficits into sharp focus. Over the last decade, the growth impact of fiscal deficits has generated large volume of both theoretical and empirical literature. Despite the lofty place of fiscal policy in the management of the economy, the Nigerian economy is yet to come on the path of sound growth and development. The behaviour of fiscal deficits in Nigeria has followed unsteady pattern, assessing the significance of the policy deficits. The actualization of sustainable economic growth is more imperative such that the country is working towards achieving the sustainable development goals. The paper adopted a descriptive method to show the trend of fiscal elements in Nigeria with the aim of determining the relationship between the variables specified. The paper concludes that fiscal operation is ineffective in providing the needed macroeconomic environment for sustainable growth. This paper further suggests that powerful pro-stability stakeholders strong enough to challenge government fiscal recklessness will need to emerge for sustainable and progressive development to be attained at all levels.